IMPLEMENTASI PRINSIP PELAYANAN PUBLIK DI KELURAHAN TASIKMADU BERDASARKAN PERATURAN PEMERINTAH NO 96 TAHUN 2012 TENTANG PELAYANAN PUBLIK - Veronika Erlin (Universitas Tribhuwana Tunggadewi, 2016)
Abstract: Principle implementation of public service is the manifestation of good governance. Therefore, the implementation of public service must be addressed from the service system. The purpose of this study is to determine the principle implementation of public service based on Government Regulation (PP) No. 96 Year 2012, and constraint/obstacle in the service in Tasikmadu Village. The research type used is qualitative. Source of data: primary and secondary data. And the data collection techniques: observation, interview, and documentation. Determination technique of informant purposive sampling, with the informant were Village Head, Section Head of public service, society. Then the data were analyzed by using the reduction, data presentation, verification. After that the data is tested using triangulation. The result of implementation the principle of public services in the Village of Tasikmadu has tried/attempted to give service although not perfect with the principles in Government Regulation No. 96 Year 2012 about the Implementation of Public Service. The existing constraints in the Village of Tasikmadu there are some indicators that have not been fully met, namely: integration and accessibility. .So it is advisable that the village government of Tasikmadu improve and perfect service, and in order to improve the both indicators have not been implemented. Keywords: Implementation of PP (Government Regulation) No. 96 Year 2012, Public Service, Accessibility of Services Abstrak: Implementasi prinsip pelayanan publik merupakan perwujudan dari kepemerintahan yang baik. Oleh karena itu implementasi pelayanan publik harus dibenahi dari sistem pelayanannya. Tujuan penelitian ini untuk mengetahui implementasi prinsip pelayanan publik sesuai PP No.96 Tahun 2012, dan hambatan dalam pelayanan dikelurahan Tasikmadu. Jenis Penelitian yang digunakan yaitu kualitatif. Sumber data: data primer dan sekunder. Dan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Teknik penentuan informan purposive sampling, dengan informan Lurah, Kasi Pelayanan umum, masyarakat. Kemudian data dianalisis menggunakan reduksi, penyajian data, verifikasi. Setelah itu data diuji menggunakan triangulasi. Hasil implementasi asas pelayanan publik di Kelurahan Tasikmadu sudah berupaya memberikan pelayanan meskipun belum sempurna dengan prinsip-prinsip dalam PP Nomor 96 Tahun 2012 Tentang Pelaksanaan Pelayanan Publik. Hambatan yang ada dikelurahan Tasikmadu ada beberapa indikator yang belum sepenuhnya terpenuhi yaitu: keterpanduan dan aksesibilitas. Sehingga disarankan agar lebih meningkatkan dan menyempurnakan pelayanan, dan memperbaiki kedua indikator yang belum terlaksana. Kata kunci: Implementasi PP No.96 Tahun 2012, Pelayanan Publik, Aksesibilitas Pelayanan